Optimization of Endo-Pectinase and Pectin Lyase Production from Wheat Bran by Bacillus pumilus using Response Surface Methodology - Tepe, Ozlem; Dursun, Arzu Y. (Gazi Univ, 2021)
Wheat bran is one of the most used agricultural residues for enzyme synthesis. It has a high organic content; thus, it causes environmental pollution. In this study, wheat bran was selected as a carbon source and it was supplemented with yeast extract and ammonium sulphate. Endo-pectinase and pectin lyase production by Bacillus pumilus was performed in a batch system. RSM was applied to examine the effects of the wheat bran, yeast extract and ammonium sulphate concentrations on the synthesis of enzymes and the dosages of these nutrients were optimized. According to the model design, the optimum conditions were 4.74% w/v wheat bran, 0.12% ammonium sulphate and 0.12% yeast extract. The high values of R-2 and R-adj(2) indicated that the fitted model showed good agreement with the predicted and actual values. In conclusion, these studies revealed that wheat bran can be used for the production of endo-pectinase and pectin lyase enzymes based on high enzyme activities.
Keywords: Endo-pectinase Optimization; Pectin lyase; Response surface methodology (RSM); Wheat bran